Characterization of genome structure of amphotropic and ecotropic wild mouse retroviruses. - Lai, M M (1982)
We studied the RNA genomes of several wild mouse type C retroviruses by using RNase T1-oligonucleotide fingerprinting. The amphotropic and ecotropic viruses of field strain 1504 produced very similar oligonucleotide fingerprints, but each also had several unique oligonucleotides. All of these unique oligonucleotides were located in the env gene region and were probably responsible for the host range differences between these viruses, as well as the lymphomagenic and paralytogenic properties of the viruses. We obtained similar results with the amphotropic and ecotropic viruses of another field strain (4070), which was isolated from a mouse from a different trapping area. The amphotropic viruses of several field strains (strains 1504, 4070, and 1313) were more closely related than the ecotropic viruses of different strains (strains 1504, 4070, and 4996). These findings suggested that the genetic sequences of the amphotropic viruses are more conserved than those of ecotropic viruses isolated from the same wild mice.